Multidecadal to millennial marine climate oscillations across the Denmark Strait (~ 66° N) over the last 2000 cal yr BP - J. T. Andrews; A. E. Jennings (Climate of the Past, 2014)
In the area of Denmark Strait (~66° N), the two modes of the North Atlantic Oscillation (NAO) and Arctic Oscillation (AO) are expressed in changes of the northward flux of Atlantic water and the southward advection of polar water in the East Iceland current. Proxies from marine cores along an environmental gradient from extensive to little or no drift ice, capture low frequency variations over the last 2000 cal yr BP. Key proxies are the weight% of calcite, a measure of surface water stratification and nutrient supply, the weight% of quartz, a measure of drift ice transport, and grain size. Records from Nansen and Kangerlussuaq fjords show variable ice-rafted debris (IRD) records but have distinct mineralogy associated with differences in the fjord catchment bedrock. A comparison between cores on either side of the Denmark Strait (MD99-2322 and MD99-2269) show a remarkable millennial-scale similarity in the trends of the weight% of calcite with a trough reached during the Little Ice Age. However, the quartz records from these two sites are quite different. The calcite records from the Denmark Strait parallel the 2000 yr Arctic summer-temperature reconstructions; analysis of the detrended calcite and quartz data reveal significant multi-decadal–century periodicities superimposed on a major environmental shift occurring ca. 1450 AD.